Efektifitas Sistem Informasi Akuntansi (SIA) dan Tata Kelola Perusahaan (GCG) Di Indonesia - Nilammadi, Wa Ode Musmiarny; Wuryani, Eni (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2025)
This study delves into how Systems for Accounting Information (AIS) influence the implementation of Good Corporate Governance (GCG) within Indonesian companies, set against the backdrop of high-profile financial scandals that have exposed critical flaws in governance practices. The research brings an objective, which is to determine whether an effective AIS can enhance GCG within companies. A quantitative research design was adopted, utilizing a survey-based approach. To gather primary data, questionnaires were disseminated among employees working in accounting departments across Surabaya. Furthermore, the data were processed using measurement model testing techniques and structural model testing with SmartPLS software. From a sequence of research steps, it has indicated that AIS brings an impactful positive influence on GCG. This shows the proof that a well-designed AIS can significantly contribute to improving GCG practices within companies. This research offers value on both academic and practical levels. From an academic perspective, it lays the groundwork for future investigations and deeper exploration on AIS and GCG. Practically, it offers companies the opportunity to enhance the performance of their corporate governance by improving the effectiveness of their AIS.